Efectiveness of Using Liveworksheets in Discovery Learning Model on Increasing Student Learning Outcomes at Class XI MIPA SMA Negeri 1 Sendana (Studies on the Subject Matter Acid-Base) - Pardan, Nur Akifah; Danial, Muhammad; Sulastry, Taty (ChemEdu, 2023)
Nur Akifah Pardan, 2022. Effectiveness Using Liveworksheets Media on Discovery Learning Outcomes of Students Class IX MIPA SMA Negeri 1 Sendana Studies on Acids and Bases. Essay. Department of Chemistry, Faculty of Mathematics and Natural Sciences. Makassar public university. (Supervised by Muhammad Danial and Taty Sulastry) This research is a pre-experimental study that aims to determine the effectiveness of Using Liveworksheets Media in the Discovery Learning Model on the Learning Outcomes of Class XI MIPA Students at SMA Negeri 1 Sendana in the Study of Acid-Base Materials. The research design used was a one group pretest-posttest design. The sample in this study were students of class XI MIPA 3 SMAN 1 Sendana obtained by simple random sampling. This study uses descriptive and inferential statistical analysis. The results of the descriptive analysis obtained the average learning outcomes before treatment of 33.88 and after treatment increased to 78.54 with an average normalized gain of 0.70 in the high category. The results of inferential statistical analysis on student learning outcomes showed that the data weren’t normally distributed so that the hypothesis test used was the Wilcoxon test with = 0.05. The results of this test obtained the value of zcount > ztable (12,99 > 1,96). Therefore, it can be concluded that using Liveworksheets on the Discovery Learning Model is effective in improving the learning outcomes of students in class XI MIPA 3 SMAN 1 Sendana on Acid-Base subject matter.